DiMaCe: Digital Management of Cemetery - Mohammad, Nurul Farahain; Razali, Azaima; Bahaludin, Hafizah (IIUM Press, 2022)
An avenue for mourning and remembrance, cemeteries play a vital role in a community regardless of their religion, race, or ethnicity. Generally, cemetery records are stored using a traditional way by pen-and-paper and there is no digitalisation of the records information system to manage them. The primitive method of Muslims cemetery record management may contribute to various misinformation thus hindering cemetery lots occupancy projection and simultaneously affecting the essentials in waqf land management. Therefore, we created a prototype dashboard to manage the cemetery data digitally. The dashboard of Digital Management of Cemetery (DiMaCe) consists of statistics of total death according to month and year, waqf land utilisation, and projection of full utilisation was built using Google Data Studio and can later be used, improved, and tailored according to requirements of end-users. This digital transformation project will assist relevant authorities in managing, monitoring, and making long-term plans for waqf lands based on the dashboard analytics and reports.